Heterogeneous wage structure effects: A partial European East-West comparison - Olga Takács; János Vincze (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
We estimate heterogeneous wage structure effects for country-pairs within the EU by the Causal Forest algorithm, then identify groups of workers with the highest and lowest discrepancies in terms of wage differentials. We find that, in the East-West comparison, age is the most consistently differentiating factor. People over 40 are most adversely treated in the East relative to the West, and especially those who have no tertiary education and work in small or medium-sized enterprises.
Keywords: J31; F66; C14; 330; Wage structure effects; Generalized Random Forest Regression; Conditional average treatment effects; Wage convergence in the EU